Development of innovation activity in American medical colleges (1914–the 1980s): a brief review - Kulichenko, Alla; Куліченко, Алла Костянтинівна (My University, 2020)
In the 20th century within the intensive development of innovations, the USA became a world leader in the field of medical education. To describe the best innovation activity we have used such research methods as analysis, synthesis, systematization, generalization of scientific and pedagogical sources of different years of the 20th and 21st centuries, as well as the method of pedagogical reconstruction and the problem-chronological one. In the article, we have highlighted three periods of the 20th century. Thus, the period of education (1914–1939) marked mandatory admission to internship; emergence of residency; in the 1930s there was a combination of education and research. The research period (1939–1965) dealt with increased attention to mental health; reducing the period of study from 4 to 3 years without reducing the curriculum; reducing the length of internship and residency; grants for basic research; the emergence of biomedical research; curriculum development, based on the study of organs and systems of the human body; the emergence of the term “multiversity”; short-term independence of medical colleges from universities. The period of medical care (1965 – the 1980s)revealed the Medicare and the Medicaid, the emergence of a new speciality – family practice; family medicine development; curriculum for future doctors of primary health care in rural areas; development and implementation of the New Pathway curriculum. In the future, we will cover the innovative activity of American medical colleges in the late 20th century and at the beginning of the 21 st century.
Keywords: American medical education; innovation activity; periodization; education; research; medical care